The physiology of tropical fishes (Elsevier, 2006)
The book presents the fish diversity of the various tropical freshwatersheds, including rivers, lakes, and dams, as well as the tropical marine enviroments. Diversity is the organizational keynote at all levels of tropocal fish biology and ecology.